The Role of Plasmacytoid Dendritic Cells in Cancers - Zhou, Binhui; Lawrence, Toby; Liang, Yinming (Frontiers in Immunology, 2021)
Plasmacytoid dendritic cells (pDCs) are a special subtype of dendritic cells with the morphology of plasma cells. pDCs produce massive amounts of type I interferon (IFN-I), which was originally found to play an extremely pivotal role in antiviral immunity. Interestingly, accumulated evidence indicates that pDCs can also play an important role in tumorigenesis. In the human body, most of the IFN-α is secreted by activated pDCs mediated by toll-like receptor (TLR) stimulation. In many types of cancer, tumors are infiltrated by a large number of pDCs, however, these pDCs exhibit no response to TLR stimulation, and reduced or absent IFN-α production. In addition, tumor-infiltrating pDCs promote recruitment of regulatory T cells (Tregs) into the tumor microenvironment, leading to immunosuppression and promoting tumor growth. In this review, we discuss recent insights into the development of pDCs and their roles in a variety of malignancies, with special emphasis on the basic mechanisms.